2005
DOI: 10.1021/jp050491f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of (CF3)2CHOCH3 Reaction with OH Radicals in an Environmental Reaction Chamber

Abstract: The atmospheric chemistry of (CF3)2CHOCH3, a possible HCFC/HFC alternative, was studied using a smog chamber/FT-IR technique. OH radicals were prepared by the photolysis of ozone in a 200-Torr H2O/O3/O2 gas mixture held in an 11.5-dm3 temperature-controlled chamber. The rate constant, k1, for the reaction of (CF3)2CHOCH3 with OH radicals was determined to be (1.40 +/- 0.28) x 10(-12) exp[(-550 +/- 60)/T] cm3 molecule(-1) s(-1) by means of a relative rate method at 253-328 K. The value of k1 at 298 K was (2.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
5
18
2
Order By: Relevance
“…The barrier height values show that hydrogen abstraction by OH radicals from the terminal -CH 2 F group is more facile than that from the -CH attached to two -CF 3 groups. This finding contradicts with the observation of Chen et al 18 that the CH attached to two -CF 3 groups is more reactive than the terminal -CH 3 towards hydrogen abstraction reactions by the OH radical in a similar compound, (CF 3 ) 2 CHOCH 3 .…”
Section: A Structure and Energeticscontrasting
confidence: 83%
See 1 more Smart Citation
“…The barrier height values show that hydrogen abstraction by OH radicals from the terminal -CH 2 F group is more facile than that from the -CH attached to two -CF 3 groups. This finding contradicts with the observation of Chen et al 18 that the CH attached to two -CF 3 groups is more reactive than the terminal -CH 3 towards hydrogen abstraction reactions by the OH radical in a similar compound, (CF 3 ) 2 CHOCH 3 .…”
Section: A Structure and Energeticscontrasting
confidence: 83%
“…The reaction of Sevoflurane with OH radicals was first studied by Brown et al 16 in 1989 and they reported a rate constant of (7.3 AE 2.2) Â 10 À14 cm 3 molecule À1 s À1 at 299 K. Subsequently, Langbein et al 8 performed another experimental study by using a relative method and they reported a significantly lower rate constant value of (2.7 AE 0.5) Â 10 À14 cm 3 molecule À1 s À1 at 298 K. Recently, this reaction has been studied experimentally by Andersen et al 17 using a smog chamber and the FTIR technique. The experimental rate constant was derived as k(OH + (CF 3 ) 2 CHOCH 2 F) = (3.9 AE 0.3) Â 10 À14 cm 3 molecule À1 s À1 at 298 K. In other reports, Chen et al 18 studied the kinetics of the reactions of OH radicals with a similar HFE, (CF 3 ) 2 CHOCH 3 , using a smog chamber and the FTIR technique at 298 AE 2 K and atmospheric pressure (760 AE 10 Torr). The atmospheric lifetime of Sevoflurane with OH radicals has been estimated to be 1.8 years.…”
Section: Introductionmentioning
confidence: 99%
“…The main sink of HFEs in the atmosphere is the reaction with OH radicals and possibly with Cl atoms in marine environments and also heavily industrialized urban areas with high levels of chloride‐containing aerosol. In both cases, the reactions proceed by H‐atom abstraction followed by the addition of O 2 to form a peroxy radical which reacts further to eventually give the corresponding hydrofluorinated esters (FESs) 2–11. Consequently, knowledge of the rate coefficients for the reactions with tropospheric oxidants like OH radicals and Cl atoms and the degradation pathways is required to estimate the persistence, fate, and harmful effects of fluoroesters in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Degradation in the troposphere is initiated by reaction with hydroxyl radicals ( • OH) to produce water and an ether radical. There are only a few published experimental studies on • OH reaction rates for this class of compounds [5][6][7], and most of them report absolute rates, which have the disadvantage of being susceptible to spurious • OH loss due to impurities or secondary products. Hsu and DeMore [8] used a relative rate technique for the reactions of • OH radicals with CF 3 OCH 3 , CF 2 HOCF 2 H, and CF 3 OCF 2 H. They found significantly slower reaction rates for the latter two, which translates to significantly longer atmospheric lifetimes than previously estimated [9].…”
Section: Introductionmentioning
confidence: 99%